Nociceptive Local Field Potentials Recorded from the Human Insula Are Not Specific for Nociception - Liberati, Giulia; Klöcker, Anne; Safronova, Marta M.; Ferrão Santos, Susana; Ribeiro Vaz, Jose-Geraldo; Raftopoulos, Christian; Mouraux, André (PLOS Biology, 2016)
The insula, particularly its posterior portion, is often regarded as a primary cortex for pain. However, this interpretation is largely based on reverse inference, and a specific involvement of the insula in pain has never been demonstrated. Taking advantage of the high spatiotemporal resolution of direct intracerebral recordings, we investigated whether the human insula exhibits local field potentials (LFPs) specific for pain. Forty-seven insular sites were investigated. Participants received brief stimuli belonging to four different modalities (nociceptive, vibrotactile, auditory, and visual). Both nociceptive stimuli and non-nociceptive vibrotactile, auditory, and visual stimuli elicited consistent LFPs in the posterior and anterior insula, with matching spatial distributions. Furthermore, a blind source separation procedure showed that nociceptive LFPs are largely explained by multimodal neural activity also contributing to non-nociceptive LFPs. By revealing that LFPs elicited by nociceptive stimuli reflect activity unrelated to nociception and pain, our results confute the widespread assumption that these brain responses are a signature for pain perception and its modulation.